Pakistan : Can Private Schools Catering to the Poor Increase Access and Improve Learning? - World Bank (World Bank, Washington, DC, 2018)
Educating children is a priority across the world, but low-income countries can face enormous challenges. Schools are often overcrowded and in disrepair. Teachers don't always show up or may not be qualified or interested in teaching. Parents hesitate to send children, especially girls, to schools that aren't close by or they may want to keep them at home to help with housework. The numbers tell the story: Worldwide, 58 million children who should be in primary school are not, despite the push for universal primary education by national governments and international organizations. In the effort to boost enrollment, raise teaching standards and strengthen school accountability, policymakers and education experts are exploring a variety of approaches, including leveraging the private and other non-governmental sectors to offer quality education to disadvantaged children.